The Oxford handbook of open innovation - Chesbrough, Henry William; Radziwon, Agnieszka; Vanhaverbeke, Wim; West, Joel (Oxford : Oxford University Press, 2023)
This handbook seeks to be the definitive reference for the large and growing field of open innovation.
This edition also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource and publisher information; title from PDF title page (viewed on January 5, 2024).
Keywords: Technological innovations -- Management; Research, Industrial -- Management; Diffusion of innovations -- Management; Business and Management; Business & Management